Comparing the EMS adopter and EMS non-adopter organizations in achieving sustainable business goals - Wang, Yizhou; Rehmani, Mahmood; Ashraf, Muhammad Raees; Farheen, Nazia; Irshad, Huda (Frontiers in Psychology, 2022)
The corporate sector has paid attention to the concept of sustainable development since the emergence of this concept in the late 1980s and the adoption of Environmental Management Systems (EMS) by many organizations is the initiative of these organizations’ exact dimensions. The focus of this research is to compare the status of EMS adopter and EMS non-adopter organizations in terms of Environmental Performance, Occupational health and safety performance, Employee Satisfaction, Operational Improvement and competitive advantage. The overall environmental performance of EMS adopter companies was approximately two times higher than non-EMS adopter companies. EMS adopter organizations’ performance was almost two times better than non-EMS adopter organizations regarding occupational health and safety. The overall Employee Satisfaction level at non-EMS adopter organizations was about three times better than at EMS adopter organizations. The EMS adopter organizations were found to have about three times performance regarding operational improvement. Regarding the competitive advantage gained by the EMS adopter companies compared to the non-EMS adopter organizations, no significant difference was observed between these two categories of organizations. However, The EMS adopter organizations seem to have a slight competitive advantage over non-adopter companies.